BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Compendium of Citrus Diseases. Editors, J. O. Whiteside, S. M. Gamsey and l. W. Timmer, Published by the American Phytopathological Society, St. Paul, Minnesota, U.S.A., 80 pp.The multiauthor edited compendium of citrus diseases is the 27th compendium, in the series of crop diseases published by the American Phytopathological Society in 1988. The compendium contains three parts one each on infectious (biotic), noninfectious (abiotic) and diseases of uncertain etiology.Leptographium Root Diseases on Conifers. Editor, T. C. Harrington and F. W. Cobb. Jr. A.P.S. Press, St. Paul, Minnesota, USA, pp. 149, 1988, US $ 30.00.The publication of the book based on the symposium entitled "Verticicladiella spp. as root pathogens of conifers" which is now called as Leptographium is a welcome sign in the field of forest pathology. The book has been reproduced directly from the papers presented in the symposium.